A REVIEW: ENERGY & WATER AUDIT: TYPES, SCOPE, METHODOLOGY AND GAPS (International Association of Biologicals and Computational Digest, 2023)
In most developing countries, the energy problems to be addressed are countering the high dependence on traditional sources of energy. An energy Audit is key to a systematic approach to decision-making in the area of energy management. The energy audit is a wide spectrum of energy study which ranges from identifying major energy problem areas to implications of alternative energy efficient measures. one must go for the energy audit to save electricity at a much lower cost. Water Audit comes into the picture in the late 80s to overcome drought-related problems, shortages, leakages and losses. Water audits provide a rational, scientific framework that categorizes all water use in your system. The standard water balance or methodology is the framework for categorizing and quantifying all water uses in the water audit. The utility should be estimating the amount of water used in this category as accurately as possible. For many systems, the water used in this category may vary over time, or it may be zero. Recommended by the [IWA and AWWA] Water Loss Committee. Distribution and its efficient use to reduce capital and operating cost as an added advantage over the optimized use of water resources with environmental protection.
Keywords: Energy audit, Energy Consumption, Save Energy, Water Audit, Save Water